Vertical transmission of Bartonella schoenbuchensis in Lipoptena cervi - de Bruin, Arnout; van Leeuwen, Arieke Docters; Jahfari, Setareh; Takken, Willem; Földvári, Mihály; Dremmel, László; Sprong, Hein; Földvári, Gábor (Parasites & vectors, 2015)
BACKGROUND: Lipoptena cervi (Diptera: Hippoboscidae) is a hematophagous ectoparasite of cervids, which is considered to transmit pathogens between animals and occasionally to humans. The principal life stage that is able to parasitize new hosts is a winged ked that just emerged from a pupa. To facilitate efficient transmission of pathogens between hosts, vertical transmission from female deer keds to their offspring is necessary. We investigated vertical transmission of several vector-borne pathogens associated with cervids. METHODS: Deer keds from several locations in Hungary were collected between 2009 and 2012. All life stages were represented: winged free-ranging adults, wingless adults collected from Capreolus capreolus and Cervus elaphus, developing larvae dissected from gravid females, and fully developed pupae. The presence of zoonotic pathogens was determined using qPCR or conventional PCR assays performed on DNA lysates. From the PCR-positive lysates, a gene fragment was amplified and sequenced for confirmation of pathogen presence, and/or pathogen species identification. RESULTS: DNA of Bartonella schoenbuchensis was found in wingless males (2%) and females (2%) obtained from Cervus elaphus, dissected developing larvae (71%), and free-ranging winged males (2%) and females (11%). DNA of Anaplasma phagocytophilum and Rickettsia species was present in L. cervi adults, but not in immature stages. DNA of Candidatus Neoehrlichia mikurensis was absent in any of the life stages of L. cervi. CONCLUSIONS: B. schoenbuchensis is transmitted from wingless adult females to developing larvae, making it very likely that L. cervi is a vector for B. schoenbuchensis. Lipoptena cervi is probably not a vector for A. phagocytophilum, Rickettsia species, and Candidatus N. mikurensis.